2008
DOI: 10.1002/art.23295
|View full text |Cite
|
Sign up to set email alerts
|

Leishmanial lipid suppresses tumor necrosis factor α, interleukin‐1β, and nitric oxide production by adherent synovial fluid mononuclear cells in rheumatoid arthritis patients and induces apoptosis through the mitochondrial‐mediated pathway

Abstract: Results. Leishmanial lipid inhibited the release of tumor necrosis factor ␣, interleukin-1␤, and NO in the culture, decreased their cytosolic protein levels, and decreased NF-B p65 levels in SFMCs, in a dosedependent manner. It had the reverse effect on interleukin-10 levels. Leishmanial lipid-induced apoptosis involved the activation of caspase 3, caspase 9, and Bax, the release of cytochrome c, the alteration of mitochondrial membrane potential, and the downregulation of Bcl-2.Conclusion. These results sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 49 publications
1
24
0
1
Order By: Relevance
“…We are also developing a new entity, i.e. leishmanial lipid, which has already been reported to have apoptosis-inducing effect in synovial cells isolated from rheumatoid arthritis patients [15]. Recently, we have reported the protective role of this lipid against Escherichia coli-induced bacterial sepsis [14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We are also developing a new entity, i.e. leishmanial lipid, which has already been reported to have apoptosis-inducing effect in synovial cells isolated from rheumatoid arthritis patients [15]. Recently, we have reported the protective role of this lipid against Escherichia coli-induced bacterial sepsis [14].…”
Section: Discussionmentioning
confidence: 98%
“…We very recently reported that the leishmanial lipid shows biological activity in in vitro and in vivo systems and also proves useful for rheumatoid arthritis patients through immune regulation [14,15]. So, we have decided to find out if the sphingolipid isolated from Leishmania donovani can also fight against cancer by inducing apoptosis with simultaneous regulation of angiogenesis and inflammatory situation in in vivo systems.…”
Section: Introductionmentioning
confidence: 97%
“…TLC was performed in chloroform-methanol-water (90/10/1) and lipid spots were visualized using iodine spray [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Aliquots of the supernatant containing nuclear protein were added to incubation wells precoated with the NF- κ B p65 DNA-binding consensus sequence, and the translocated p65 subunit present in nuclear lysate was assayed [22]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation